Dynamic geometrical configuration predictions during robotic manipulation for automated cable assembly. (July 2022) - Du, Hongwang; Jiang, Qinwen; Xiong, Wei
Abstract: During robotic manipulation, flexible cables are significantly more difficult to model than rigid objects, and they cause a computationally intensive problem. This paper proposes a viscoelastic rod model to predict the dynamics of cable assembly. The spatial shape of the cable could be decomposed into the position of the centerline and the rotation of the cross section. The interaction forces and bending moments of a cable under various boundary conditions were analyzed using a discrete finite element method. Gravitational effects and friction dissipation were also considered. An improved semi-implicit Euler method was employed to solve the model, and the cable motion was simulated for different boundary conditions. A dynamic motion experimental bench was built based on the binocular vision measurement method of cable centerline projection, and the actual shape of the cable was measured. The average error between the actual and simulated coordinates for each discrete cable point along the centerline was within 5%. Experimental results verified the algorithm and the modeling method. Graphical Abstract: ga1 Highlights: A viscoelastic rod model is proposed to predict the dynamics of the cable assembly. Cable motion under different boundary conditions is analyzed. The average error of coordinates of discrete points of cable simulation and actual shape is less than 5%.